Anisotropy-magnetic susceptibility from the Krems Wachtberg archaeological Site (Austria) and high temperature susceptibility - Zeeden, Christian; Hambach, Ulrich; Händel, Marc (Supplement to: Zeeden, C et al. (2015): Loess magnetic fabric of the Krems-Wachtberg archaeological site. Quaternary International, 372, 188-194, https://doi.org/10.1016/j.quaint.2014.11.001, 2014)
The loess sediment embedding the main Gravettian layer at the Krems-Wachtberg archaeological site facilitates exceptional preservation. To gain insight in the sedimentation process before and after the Paleolithic settlement, the magnetic fabric (preferential orientation of magnetic particles) of loess of the Krems-Wachtberg site is investigated. Magnetic fabric properties clearly show an eolian origin of the loess, but may indicate some relocation in the meter above the cultural layer. The magnetic fabric properties can be divided into three intervals, the top interval shows lowest foliation and inconsistent magnetic fabric directions. The middle interval around the main cultural layer shows low foliation, but a clear preferential NW - SE direction of the lineation. This lineation is interpreted as preferential direction of the eolian loess accumulation from the South-East. The interval below ca. 0.5 m underneath the main find horizon shows a northeast-southwest lineation, but an imbrication suggesting that sediment accumulation occurred perpendicular to this direction, similar to the interval around the find horizon.